PD-L1 Immunoexpression on Cytology and its Paired Comparison with Histopathology in Lung Carcinoma - Chandra, Smita; Dhawan, Vishesh; Kediya, Ayushi (Annals of Pathology and Laboratory Medicine, 2023)
Background Cell blocks are being increasingly used as a less invasive diagnostic procedure for various ancillary tests like immunohistochemistry. The assays programmed death ligand-1 (PD-L1) is one such companion diagnostic test playing a role in progression of lung cancer. The present study was carried out to examine efficacy of cell blocks for PD-L1 expression in lung cancer patients. Methods Over the course of a year, our pathology department conducted this prospective study and included newly diagnosed lung carcinoma cases on cytopathological examination. Tumor Proportion Score (TPS) was used for grading cell membrane PD-L1 positivity. Excel sheet was used for compiling and analysing the data using the IBM SPSS software version 28 (Statistical Package for Social Sciences) Chicago, USA. Result The study included 36 cases in which cell blocks and paired histopathological sections were studied, of which 1 cell block was inadequate for reporting. PD-L1 expression was negative in 57%, low grade in 40% and high grade in 3% cases. It was seen in 40% squamous cell carcinoma, 40% adenocarcinoma and 20% small cell carcinoma. Among them, 11 were true positive, 5 were false positive, 3 were false negative and 16 were true negative. With a 78.5% sensitivity, 76% specificity, 68.7% positive predictive value and 84.2% negative predictive value, PD-L1 on cell blocks correlated with paired histopathological sections in 77% of cases in our study. Conclusion: Cell blocks can be utilized for evaluating PD-L1 expression in lung carcinoma and act as an efficient and trustworthy substitute to routine histopathological techniques.